Injectable hydrogel with redox activity and electroactivity as well as preparation method and application of injectable hydrogel
By preparing injectable hydrogels with redox activity and electroactive, the problem that existing hydrogels are difficult to establish stable electrical coupling and improve the survival status of cardiomyocytes in the treatment of heart failure is solved, and the effect of myocardial tissue repair and regeneration is achieved.
Patent Information
- Application Number
- CN202510409267.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-02
AI Technical Summary
When used in the treatment of heart failure, it is difficult to establish stable electrical coupling, and in the adverse microenvironment of the infarct myocardium, it is difficult to improve the survival status of surrounding surviving cardiomyocytes, which is not conducive to inducing myocardial tissue repair and regeneration.
An injectable hydrogel with redox activity and electroactive is used. The preparation method includes reacting methacrylic anhydride and polysaccharide molecules to form a double bond functional polymer, reacting dopamine-modified metal frame compound and iron salt to form a nanofiller, and dispersing it in a solvent with the active polypeptide and photoinitiator for photocuring and crosslinking, forming a hydrogel with conductive and redox activity.
The hydrogel has excellent injectable and conductive properties, can simulate the catalytic activity of natural enzymes, effectively eliminate reactive oxygen species, enhance electrical conduction at infarction sites, and achieve effective recovery of cardiac function.
Smart Images

Figure CN119909007A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical materials, and in particular to an injectable hydrogel with redox activity and electrical activity, and a preparation method and application thereof. Background Art
[0002] Heart failure refers to a clinical syndrome caused by a variety of heart diseases, which is mainly manifested by a decrease in the heart's pumping function. Many cardiovascular diseases can cause the myocardium to weaken in its ability to relax and contract, such as hypertension, dilated cardiomyopathy, and valvular heart disease. Heart failure is the end-stage manifestation of various heart diseases. From an epidemiological perspective, the prevalence, incidence, and mortality of heart failure are all very high.
[0003] There are currently three main clinical treatments for heart failure: drug therapy, left ventricular assist device (LVAD) and heart transplantation. Drug therapy mainly focuses on lowering blood pressure, increasing myocardial contractility (positive inotropic drugs), inhibiting sympathetic nerve activity and anticoagulation, which can effectively alleviate patient symptoms, but long-term medication has limited effects. Left ventricular assist devices can improve patients' hemodynamics, but there are risks of multiple complications, including embolism and infection. Heart transplantation is currently an effective treatment for patients with end-stage heart failure, but this treatment method is also limited due to limited donors.
[0004] Injectable hydrogels are an advanced method for treating heart failure based on the concepts of tissue engineering and regenerative medicine. However, most hydrogels lack conductive properties and it is difficult to establish stable electrical coupling. In addition, in view of the adverse microenvironment of low pH, high ROS and infiltration of inflammatory factors in the infarcted myocardium, hydrogels that lack the ability to scavenge reactive oxygen species are difficult to improve the survival status of the surrounding surviving myocardial cells, which is not conducive to inducing myocardial tissue repair and regeneration. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide an injectable hydrogel with redox activity and electrical activity, and a preparation method and application thereof, so as to solve the problems that the existing injectable hydrogels are difficult to establish stable electrical coupling when used in the treatment of heart failure, and the adverse microenvironment of low pH, high ROS and inflammatory factor infiltration in the infarcted myocardium is difficult to improve the survival state of the surrounding surviving myocardial cells, which is not conducive to inducing myocardial tissue repair and regeneration.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: A method for preparing an injectable hydrogel having redox activity and electroactivity, comprising the following steps: (1) Methacrylic anhydride and polysaccharide molecules are reacted in a solvent to prepare a double-bond functional polymer; (2) Dopamine is first prepolymerized in a solvent, and then a metal framework compound is added to carry out a polymerization reaction to obtain a dopamine-modified metal framework compound; (3) reacting the dopamine-modified metal framework compound obtained in step (2), 4-ethylenedioxythiophene and iron salt in a solvent, collecting the precipitate, and preparing a nanofiller; (4) The double-bond functional polymer obtained in step (1), the active polypeptide, the photoinitiator and the nanofiller obtained in step (3) are dispersed in a solvent and subjected to photocuring and cross-linking to obtain a nanostructured polymer.
[0007] The beneficial effects of the present invention are as follows: the preparation conditions of the present invention are mild, the gelation is rapid, the preparation method is simple, the prepared hydrogel has excellent injectability and electrical conductivity, can simulate the catalytic activity of natural enzymes, can achieve active oxygen scavenging in the early stage of myocardial ischemia, enhance electrical conduction at the infarction site, and achieve effective recovery of cardiac function.
[0008] Furthermore, in step (1), the polysaccharide molecule is sodium alginate, the solvent is water, the reaction temperature is 0-10°C, and the reaction time is 20-30 h.
[0009] Preferably, in step (1), the reaction temperature is 4°C and the reaction time is 24 h.
[0010] Furthermore, the concentration of sodium alginate in the reaction solution of step (1) is 0.5 w / v %-2 w / v %; and the volume ratio of methacrylic anhydride to the solvent is (3-10): (80-120).
[0011] Preferably, the concentration of alginic acid in the reaction solution of step (1) is 1 w / v %; and the volume ratio of methacrylic anhydride to the solvent is 8:100.
[0012] Furthermore, in step (1), the pH of the reaction solution is adjusted to 8-9 by using NaOH solution.
[0013] Furthermore, the metal framework compound in step (2) is prepared by the following steps: (a) reflux methyl p-formylbenzoate and pyrrole in a solvent to obtain a purple solid product; (b) refluxing the purple solid product obtained in step (a) and manganese chloride tetrahydrate in a solvent, then adding water and stirring after the solution is cooled to room temperature, and collecting the precipitate; (c) first dissolving the precipitate obtained in step (b) in an organic solvent, then mixing with a KOH aqueous solution and refluxing, then removing the organic solvent by rotary evaporation, adding water for redissolution, and finally adding an acidic solution to precipitate and collect a solid to obtain a purple powder product; (d) zirconium oxychloride octahydrate, benzoic acid and the purple powder product obtained in step (c) are mixed in a solvent for reaction, and the precipitate is collected to obtain the product.
[0014] Further, in step (a), the solvent is propionic acid and the reflux time is 10-15 h; In step (b), the solvent is N,N-dimethylformamide, the reflux time is 4-8 h, and the stirring time is 30-90 min; In step (c), the organic solvent is a mixed solvent consisting of tetrahydrofuran and methanol, and the mixing and refluxing time is 10-15 h; The temperature of the mixed reaction in step (d) is 80-100° C. and the time is 4-6 h.
[0015] Preferably, the reflux time in step (a) is 12 h; In step (b), the reflux time is 6 h and the stirring time is 60 min; The mixing reflux time in step (c) is 12 h; The temperature of the mixed reaction in step (d) is 90° C. and the time is 5 h.
[0016] Furthermore, in step (a), the mass volume ratio of methyl paraformylbenzoate, pyrrole and solvent is 10-20 g: 4-8 mL: 150-250 mL.
[0017] Preferably, in step (a), the mass volume ratio of methyl paraformylbenzoate, pyrrole and solvent is 14 g: 6 mL: 200 mL.
[0018] Furthermore, in step (b), the mass volume ratio of the purple solid product, manganese chloride tetrahydrate and the solvent is 0.4-1.0 g: 2.0-3.0 g: 50-150 mL.
[0019] Preferably, in step (b), the mass volume ratio of the purple solid product, manganese chloride tetrahydrate and the solvent is 0.854 g:2.5 g:100 mL.
[0020] Furthermore, in step (c), the organic solvent is a mixed solvent consisting of tetrahydrofuran and methanol in a volume ratio of (20-30): (20-30); and the mass ratio of the precipitate to KOH is (0.5-1.0): (2-5).
[0021] Preferably, in step (c), the organic solvent is a mixed solvent consisting of tetrahydrofuran and methanol in a volume ratio of 25:25; and the mass ratio of the precipitate to KOH is 0.75:2.63.
[0022] Furthermore, in step (d), the mass volume ratio of zirconium oxychloride octahydrate, benzoic acid, purple powder product and solvent is 30-40 mg: 250-500 mg: 10-20 mg: 10-20 mL.
[0023] The beneficial effects of adopting the above further technical scheme are as follows: the MOF nanofiller based on manganese porphyrin of the present invention highly simulates the coordination structure of natural superoxide dismutase SOD2, and as the redox active center, the manganese porphyrin metal organic connector has bionic SOD- and CAT-like activities. Manganese porphyrin is used as a catalytic unit for orderly assembly, and highly positive zirconium oxygen clusters are used as metal connection points to increase the redox potential of its catalytic center Mn III, and the obtained MOF nanofiller with redox activity can effectively remove active oxygen and free radicals.
[0024] Furthermore, in step (2), the solvent is a Tris-HCl solution, the prepolymerization time is 20-40 min, and the polymerization reaction time is 10-15 h.
[0025] Preferably, the prepolymerization time is 30 min and the polymerization reaction time is 12 h.
[0026] Furthermore, in step (2), the mass volume ratio of dopamine, metal framework compound and solvent is 50-100 mg: 150-250 mg: 50-150 mL.
[0027] Preferably, in step (2), the mass volume ratio of dopamine, metal framework compound and solvent is 100 mg:200 mg:100 mL.
[0028] Furthermore, in step (3), the solvent is ethanol, the iron salt is ferric chloride hexahydrate, and the reaction conditions are stirring in an ice bath for 20-30 h.
[0029] Furthermore, in step (3), the mass volume ratio of the dopamine-modified metal framework compound, the iron salt, 4-ethylenedioxythiophene and the solvent is 250-350 mg: 3-5 g: 200-250 μL: 30-50 mL.
[0030] Preferably, in step (3), the mass volume ratio of the dopamine-modified metal framework compound, the iron salt, 4-ethylenedioxythiophene and the solvent is 296.4 mg: 4 g: 228 μL: 40 mL.
[0031] The beneficial effects of adopting the above further technical scheme are as follows: in order to solve the problem of poor conductivity of MOF materials, the present invention in situ polymerizes a conductive polymer after modifying the surface of the MOF material with a polydopamine adhesion layer. The conductive polymer molecular chain serves as a bridge for charge transfer, releases electrons into the electrolyte during the electrochemical process, enhances the Faraday process on the interface, and thus contributes to pseudocapacitance. When the nanofiller is loaded in the hydrogel, the hydrogel is given redox activity and electrical activity at the same time.
[0032] Furthermore, the amino acid sequence of the active polypeptide in step (4) is shown in SEQ ID NO.1: CGERGAPGFRGPAGPNGIPGEKGPAGERGAP (SEQ ID NO. 1).
[0033] The beneficial effects of adopting the above further technical scheme are as follows: the present invention modifies the cell adhesive polypeptide on the natural polysaccharide molecular skeleton by covalent cross-linking, thereby enhancing the interaction between the hydrogel matrix and cells, improving the affinity between the hydrogel and tissue, and laying a good foundation for the realization of various functions of the hydrogel platform.
[0034] Further, in step (4), the solvent is water; The concentration of the double bond functional polymer in the reaction solution is 1 w / v %-5 w / v %; The concentration of the photoinitiator is 0.1 w / v %-0.5 w / v %; The mass ratio of active polypeptide to double-bond functional polymer is 0.1:1-1:1; The concentration of nanofillers was 10-80 μg / mL; The conditions for photocuring crosslinking are: irradiation with 350-450 nm ultraviolet light for 30-60 s.
[0035] The beneficial effects of adopting the above further technical scheme are as follows: the present invention utilizes the addition reaction of double bonds under ultraviolet light to crosslink and gel, the gelling conditions are mild, the gelling is rapid, and the preparation method is simple, so that the hydrogel has excellent rheological properties and injectability.
[0036] An injectable hydrogel with redox activity and electrical activity is prepared by the preparation method.
[0037] Application of the above injectable hydrogel with redox activity and electroactivity in the preparation of drugs for the treatment of heart failure.
[0038] The present invention has the following beneficial effects: (1) The present invention enhances the interaction between the hydrogel matrix and cells and improves the affinity between the hydrogel and tissue by covalently cross-linking the cell adhesive polypeptide on the natural polysaccharide molecular skeleton, thus laying a good foundation for the realization of various functions of the hydrogel platform.
[0039] (2) In the present invention, manganese porphyrins are orderly assembled as catalytic units, and highly positively charged zirconium oxygen clusters are used as metal connection points to increase the redox potential of the catalytic center Mn III. The resulting MOF nanofiller with redox activity can effectively remove active oxygen and free radicals.
[0040] (3) The present invention modifies the surface of the MOF material with a polydopamine adhesion layer and then in situ polymerizes a conductive polymer to impart redox activity and electrical activity to the hydrogel.
[0041] (4) The gelation conditions of the present invention are mild, the gelation is rapid, the preparation method is simple, and the prepared hydrogel has excellent rheological properties and injectability.
[0042] (5) The hydrogel prepared by the present invention has good injection performance and electrical conductivity, and has the catalytic activity of simulating natural enzymes, which can achieve active oxygen scavenging in the early stage of myocardial ischemia, enhance electrical conduction in the infarction site, and ultimately achieve the purpose of restoring cardiac function. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a test diagram of the gelation and injectability of the hydrogel prepared in Example 1, wherein i) and ii) are tests of the gelation, and iii) is a test of the injectability; Figure 2 The rheological behavior diagram of the hydrogel prepared in Example 1, wherein a is the rheological property test result, and b is the self-healing property test result; Figure 3 The conductive properties test results of the hydrogels prepared in Example 1, Examples 4-5 and Comparative Example 1 are shown; Figure 4 The microscopic morphology and element distribution diagram of the nanofiller PEDOT@PMOF obtained in Example 1, wherein a is the microscopic morphology diagram and b is the element distribution diagram; Figure 5 The graph is a test result of the active oxygen scavenging ability of the nanofiller PEDOT@PMOF obtained in Example 1, wherein a is a UV absorption spectrum of the SOD-like performance of the nanofiller PEDOT@PMOF at different concentrations, b is the EPR result of the SOD-like performance of the nanofiller PEDOT@PMOF, c is the EPR result of the scavenging efficiency of the nanofiller PEDOT@PMOF for hydroxyl radicals, and d is a UV absorption spectrum of the CAT enzyme-like performance of the nanofiller PEDOT@PMOF; Figure 6 This is a diagram showing the results of an animal therapeutic ultrasound experiment on the hydrogel prepared in Example 1; Figure 7 This is a diagram of the tissue section results of the animal treatment of the hydrogel prepared in Example 1; Figure 8 The result diagram of the hydrogel prepared in Example 1 can effectively reduce the susceptibility to arrhythmia, wherein ac are the arrhythmia results of the sham operation group, the myocardial infarction model group and the experimental group under electrical stimulation, and d is the arrhythmia induction quotient result. DETAILED DESCRIPTION
[0044] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0045] Embodiment 1: A method for preparing an injectable hydrogel having redox activity and electroactivity, comprising the following steps: (1) Synthesis of double-bond functionalized alginate (AlgMA) First, 100 mL of 1 w / v % sodium alginate aqueous solution was prepared under sterile conditions. Then, 8 mL of methacrylic anhydride was slowly added at 4°C. The pH value of the solution was controlled at 8-9 with 5 mol / L NaOH. After reacting for 24 h, the solution was dialyzed in water for 3 days and freeze-dried for 3 days to obtain AlgMA.
[0046] (2) Synthesis of active peptide T16 The thiol-terminated polypeptide T16 was synthesized by standard solid phase synthesis method. The amino acid sequence is SEQ ID NO. 1: CGERGAPGFRGPAGPNGIPGEKGPAGERGAP.
[0047] (3) Synthesis of metal framework compound MOF (PCN222-Mn) First, 1.4 g of methyl p-formylbenzoate was dissolved in 200 mL of propionic acid, and 6 mL of pyrrole was added dropwise. The mixed solution was refluxed in the dark for 12 h. After the reaction was completed, the mixture was cooled to room temperature, filtered and washed three times with methanol and tetrahydrofuran, and a purple solid product A was obtained by suction filtration.
[0048] Then, 0.854 g of product A and 2.5 g of manganese chloride tetrahydrate were dissolved in 100 mL of DMF, and the mixed solution was refluxed in the dark for 6 h. After the reaction was completed, the solution was cooled to room temperature, 150 mL of H2O was added and stirred for 1 h. The precipitate B precipitated in the solution was washed with water and filtered three times to obtain.
[0049] Then, 0.75 g of precipitate B was dissolved in a mixed solution consisting of 25 mL of tetrahydrofuran (THF) and 25 mL of methanol (MeOH), to which 25 mL of KOH (2.63 g, 46.95 mmol) aqueous solution was added, and the resulting mixture was heated to reflux for 12 h. After the mixture was cooled to room temperature, THF and MeOH were removed by rotary evaporation; additional water was added to the system after rotary evaporation, and the mixture was heated until the solid was completely dissolved, followed by the addition of 1 mol / L HCl solution to gradually precipitate the solid, and the HCl solution was continued to be added until no new solid precipitated, and the precipitate was collected by filtration, washed with water and dried in vacuo to obtain a purple powder product C.
[0050] Finally, zirconium oxychloride octahydrate (30 mg), benzoic acid (0.28 g) and product C (10.98 mg) were dissolved in 14 mL N,N-dimethylformamide (DMF) and stirred at 90 °C for 5 h. After the reaction, the mixture was cooled to room temperature and collected by centrifugation. The nanoparticles were washed three times with DMF and deionized water respectively to obtain PCN22-Mn.
[0051] (4) Preparation of dopamine-modified PCN222-Mn First, 100 mg of dopamine was dissolved in 100 mL of Tris-HCl solution with a pH of 8.5 and prepolymerized for 30 min. Then, 200 mg of MOF was added to the prepolymerization solution and polymerized for 12 h. Finally, the mixture was washed with ethanol three times to obtain dopamine-modified PCN222-Mn, which was recorded as PMOF.
[0052] (5) Preparation of nanofiller PEDOT@PMOF First, PMOF (296.4 mg) and EDOT (228 μL) were dispersed in ethanol (30 mL) under strong stirring, and then ferric chloride hexahydrate ethanol solution (4 g, 10 mL) was added dropwise and stirred in an ice bath for 24 h. Finally, the nanofiller PEDOT@PMOF was obtained after washing with deionized water and centrifugation.
[0053] (6) Preparation of hydrogel AlgMA (50 mg), active peptide T16 (5 mg), photoinitiator LAP (5 mg) and PEDOT@PMOF nanofiller (20 μg) were uniformly dispersed in 1 mL of water and then irradiated with 405 nm ultraviolet light for 45 s to cross-link into a gel, thereby preparing an injectable hydrogel with redox activity and electroactivity.
[0054] Embodiment 2: A method for preparing an injectable hydrogel having redox activity and electroactivity, comprising the following steps: (1) Synthesis of double-bond functionalized alginate (AlgMA) First, 100 mL of 1 w / v % sodium alginate aqueous solution was prepared under sterile conditions. Then, 5 mL of methacrylic anhydride was slowly added at 4°C. The pH value of the solution was controlled at 8-9 with 5 mol / L NaOH. After reacting for 24 h, the solution was dialyzed in water for 3 days and freeze-dried for 3 days to obtain AlgMA.
[0055] (2) Synthesis of active peptide T16 The thiol-terminated polypeptide T16 was synthesized by standard solid phase synthesis method. The amino acid sequence is SEQ ID NO. 1: CGERGAPGFRGPAGPNGIPGEKGPAGERGAP.
[0056] (3) Synthesis of metal framework compound MOF (PCN222-Mn) First, 1.4 g of methyl p-formylbenzoate was dissolved in 200 mL of propionic acid, and 8 mL of pyrrole was added dropwise. The mixed solution was refluxed in the dark for 12 h. After the reaction was completed, the mixture was cooled to room temperature, filtered and washed three times with methanol and tetrahydrofuran, and a purple solid product A was obtained by suction filtration.
[0057] Then, 0.427 g of product A and 2.0 g of manganese chloride tetrahydrate were dissolved in 100 mL of DMF, and the mixed solution was refluxed in the dark for 6 h. After the reaction was completed, the solution was cooled to room temperature, 150 mL of H2O was added and stirred for 1 h. The precipitate B precipitated in the solution was washed with water and filtered three times to obtain.
[0058] Then, 0.75 g of precipitate B was dissolved in a mixed solution consisting of 25 mL of tetrahydrofuran (THF) and 25 mL of methanol (MeOH), to which 25 mL of KOH (3.95 g) aqueous solution was added, and the resulting mixture was heated to reflux for 12 h. After the mixture was cooled to room temperature, THF and MeOH were removed by rotary evaporation; additional water was added to the system after rotary evaporation, and the mixture was heated until the solid was completely dissolved, followed by the addition of 1 mol / L HCl solution to gradually precipitate the solid, and the HCl solution was continued to be added until no new solid precipitated, and the precipitate was collected by filtration, washed with water and dried in vacuo to obtain a purple powder product C.
[0059] Finally, zirconium oxychloride octahydrate (30 mg), benzoic acid (0.4 g) and product C (10.98 mg) were dissolved in 14 mL N,N-dimethylformamide (DMF) and stirred at 90 °C for 5 h. After the reaction, the mixture was cooled to room temperature and collected by centrifugation. The nanoparticles were washed three times with DMF and deionized water respectively to obtain PCN22-Mn.
[0060] (4) Preparation of dopamine-modified PCN222-Mn First, 75 mg of dopamine was dissolved in 100 mL of Tris-HCl solution with a pH of 8.5 and prepolymerized for 30 min. Then, 200 mg of MOF was added to the prepolymerization solution and polymerized for 12 h. Finally, the mixture was washed with ethanol three times to obtain dopamine-modified PCN222-Mn, which was recorded as PMOF.
[0061] (5) Preparation of nanofiller PEDOT@PMOF First, PMOF (296.4 mg) and 4-ethylenedioxythiophene (EDOT, 228 μL) were dispersed in ethanol (30 mL) under strong stirring, and then ferric chloride hexahydrate ethanol solution (4 g, 10 mL) was added dropwise and stirred in an ice bath for 24 h. Finally, the nanofiller PEDOT@PMOF was obtained after washing with deionized water and centrifugation.
[0062] (6) Preparation of hydrogel AlgMA (50 mg), active peptide T16 (5 mg), photoinitiator LAP (2.5 mg) and PEDOT@PMOF nanofiller (20 μg) were uniformly dispersed in 1 mL of water and then irradiated with 405 nm ultraviolet light for 30 s to cross-link into a gel, thereby preparing an injectable hydrogel with redox activity and electroactivity.
[0063] Embodiment 3: A method for preparing an injectable hydrogel having redox activity and electroactivity, comprising the following steps: (1) Synthesis of double-bond functionalized alginate (AlgMA) First, 100 mL of 1 w / v % sodium alginate aqueous solution was prepared under sterile conditions. Then, 3 mL of methacrylic anhydride was slowly added at 4°C. The pH value of the solution was controlled at 8-9 with 5 mol / L NaOH. After reacting for 24 h, the solution was dialyzed in water for 3 days and freeze-dried for 3 days to obtain AlgMA.
[0064] (2) Synthesis of active peptide T16 The thiol-terminated polypeptide T16 was synthesized by standard solid phase synthesis method. The amino acid sequence is SEQ ID NO. 1: CGERGAPGFRGPAGPNGIPGEKGPAGERGAP.
[0065] (3) Synthesis of metal framework compound MOF (PCN222-Mn) First, 1.4 g of methyl p-formylbenzoate was dissolved in 200 mL of propionic acid, and 4 mL of pyrrole was added dropwise. The mixed solution was refluxed in the dark for 12 h. After the reaction was completed, the mixture was cooled to room temperature, filtered and washed three times with methanol and tetrahydrofuran, and a purple solid product A was obtained by suction filtration.
[0066] Then, 0.854 g of product A and 3.0 g of manganese chloride tetrahydrate were dissolved in 100 mL of DMF, and the mixed solution was refluxed in the dark for 6 h. After the reaction was completed, the solution was cooled to room temperature, 150 mL of H2O was added and stirred for 1 h. The precipitate B precipitated in the solution was washed with water and filtered three times to obtain.
[0067] Then 0.5 g of precipitate B was dissolved in a mixed solution consisting of 25 mL of tetrahydrofuran (THF) and 25 mL of methanol (MeOH), to which 25 mL of KOH (2.63 g, 46.95 mmol) aqueous solution was added, and the resulting mixture was heated to reflux for 12 h. After the mixture was cooled to room temperature, THF and MeOH were removed by rotary evaporation; additional water was added to the system after rotary evaporation, and the mixture was heated until the solid was completely dissolved, followed by the addition of 1 mol / L HCl solution to gradually precipitate the solid, and the HCl solution was continued to be added until no new solid precipitated, and the precipitate was collected by filtration, washed with water and dried in vacuo to obtain a purple powder product C.
[0068] Finally, zirconium oxychloride octahydrate (50 mg), benzoic acid (0.5 g) and product C (18.3 mg) were dissolved in 14 mL N,N-dimethylformamide (DMF) and stirred at 90 °C for 5 h. After the reaction, the mixture was cooled to room temperature and collected by centrifugation. The nanoparticles were washed three times with DMF and deionized water respectively to obtain PCN22-Mn.
[0069] (4) Preparation of dopamine-modified PCN222-Mn First, 50 mg of dopamine was dissolved in 100 mL of Tris-HCl solution with a pH of 8.5 and prepolymerized for 30 min. Then, 200 mg of MOF was added to the prepolymerization solution and polymerized for 12 h. Finally, the mixture was washed with ethanol three times to obtain dopamine-modified PCN222-Mn, which was recorded as PMOF.
[0070] (5) Preparation of nanofiller PEDOT@PMOF First, PMOF (296.4 mg) and EDOT (228 μL) were dispersed in ethanol (30 mL) under strong stirring, and then ferric chloride hexahydrate ethanol solution (4 g, 10 mL) was added dropwise and stirred in an ice bath for 24 h. Finally, the nanofiller PEDOT@PMOF was obtained after washing with deionized water and centrifugation.
[0071] (6) Preparation of hydrogel AlgMA (50 mg), active peptide T16 (10 mg), photoinitiator LAP (5 mg) and PEDOT@PMOF nanofiller (20 μg) were uniformly dispersed in 1 mL of water and then irradiated with 405 nm ultraviolet light for 60 s to cross-link into a gel, thereby preparing an injectable hydrogel with redox activity and electroactivity.
[0072] Embodiment 4: A method for preparing an injectable hydrogel having redox activity and electroactivity, comprising the following steps: The preparation method is the same as that of Example 1, except that the mass of the PEDOT@PMOF nanofiller in step (6) is changed to 10 μg.
[0073] Embodiment 5: A method for preparing an injectable hydrogel having redox activity and electroactivity, comprising the following steps: The preparation method is the same as that of Example 1, except that the mass of the PEDOT@PMOF nanofiller in step (6) is changed to 40 μg.
[0074] Comparative Example 1: A method for preparing an injectable hydrogel comprises the following steps: (1) Synthesis of double-bond functionalized alginate (AlgMA) First, 100 mL of 1 w / v % sodium alginate aqueous solution was prepared under sterile conditions. Then, 8 mL of methacrylic anhydride was slowly added at 4°C. The pH value of the solution was controlled at 8-9 with 5 mol / L NaOH. After reacting for 24 h, the solution was dialyzed in water for 3 days and freeze-dried for 3 days to obtain AlgMA.
[0075] (2) Synthesis of active peptide T16 The thiol-terminated polypeptide T16 was synthesized by standard solid phase synthesis method. The amino acid sequence is SEQ ID NO. 1: CGERGAPGFRGPAGPNGIPGEKGPAGERGAP.
[0076] (3) Preparation of hydrogel AlgMA (50 mg), active peptide T16 (5 mg) and photoinitiator LAP (5 mg) were evenly dispersed in 1 mL of water and then irradiated with 405 nm ultraviolet light for 45 s to cross-link into a gel to prepare the injectable hydrogel TAlg.
[0077] Comparative Example 2: A method for preparing an injectable hydrogel comprises the following steps: (1) Synthesis of double-bond functionalized alginate (AlgMA) First, 100 mL of 1 w / v % sodium alginate aqueous solution was prepared under sterile conditions. Then, 8 mL of methacrylic anhydride was slowly added at 4°C. The pH value of the solution was controlled at 8-9 with 5 mol / L NaOH. After reacting for 24 h, the solution was dialyzed in water for 3 days and freeze-dried for 3 days to obtain AlgMA.
[0078] (2) Synthesis of active peptide T16 The thiol-terminated polypeptide T16 was synthesized by standard solid phase synthesis method. The amino acid sequence is SEQ ID NO. 1: CGERGAPGFRGPAGPNGIPGEKGPAGERGAP.
[0079] (3) Synthesis of metal framework compound MOF (PCN222-Mn) First, 1.4 g of methyl p-formylbenzoate was dissolved in 200 mL of propionic acid, and 6 mL of pyrrole was added dropwise. The mixed solution was refluxed in the dark for 12 h. After the reaction was completed, the mixture was cooled to room temperature, filtered and washed three times with methanol and tetrahydrofuran, and a purple solid product A was obtained by suction filtration.
[0080] Then, 0.854 g of product A and 2.5 g of manganese chloride tetrahydrate were dissolved in 100 mL of DMF, and the mixed solution was refluxed in the dark for 6 h. After the reaction was completed, the solution was cooled to room temperature, 150 mL of H2O was added and stirred for 1 h. The precipitate B precipitated in the solution was washed with water and filtered three times to obtain.
[0081] Then, 0.75 g of precipitate B was dissolved in a mixed solution consisting of 25 mL of tetrahydrofuran (THF) and 25 mL of methanol (MeOH), to which 25 mL of KOH (2.63 g, 46.95 mmol) aqueous solution was added, and the resulting mixture was heated to reflux for 12 h. After the mixture was cooled to room temperature, THF and MeOH were removed by rotary evaporation; additional water was added to the system after rotary evaporation, and the mixture was heated until the solid was completely dissolved, followed by the addition of 1 mol / L HCl solution to gradually precipitate the solid, and the HCl solution was continued to be added until no new solid precipitated, and the precipitate was collected by filtration, washed with water and dried in vacuo to obtain a purple powder product C.
[0082] Finally, zirconium oxychloride octahydrate (30 mg), benzoic acid (0.28 g) and product C (10.98 mg) were dissolved in 14 mL N,N-dimethylformamide (DMF) and stirred at 90 °C for 5 h. After the reaction, the mixture was cooled to room temperature and collected by centrifugation. The nanoparticles were washed three times with DMF and deionized water respectively to obtain PCN22-Mn.
[0083] (4) Preparation of dopamine-modified PCN222-Mn First, 100 mg of dopamine was dissolved in 100 mL of Tris-HCl solution with a pH of 8.5 and prepolymerized for 30 min. Then, 200 mg of MOF was added to the prepolymerization solution and polymerized for 12 h. Finally, the mixture was washed with ethanol three times to obtain dopamine-modified PCN222-Mn, which was recorded as PMOF.
[0084] (5) Preparation of hydrogel AlgMA (50 mg), active peptide T16 (5 mg), photoinitiator LAP (5 mg) and PMOF (20 μg) were evenly dispersed in 1 mL of water and then irradiated with 405 nm ultraviolet light for 45 s to cross-link into a gel, thereby preparing an injectable hydrogel with redox activity and electroactivity.
[0085] Test example: 1. Gelation and injectability The gelling properties of the hydrogel prepared in Example 1 were tested by needle injection.
[0086] The experimental results are as follows Figure 1 As shown, the results show that the hydrogel prepared in Example 1 of the present invention can be injected from a 27G needle, proving that the hydrogel prepared in the present invention has good injectability.
[0087] 2. Mechanical properties and electrical conductivity The rheological properties of the hydrogel prepared in Example 2 of the present invention were tested by an MCR302 rheometer, and a double concentric cylinder geometry with a gap of 1 mm was used for steady-state shear flow at 37°C. The oscillation frequency of the strain scan was 1 Hz, and the strain was 0.1-1000%. In the self-healing experiment, an alternating step strain scan experiment (large strain: 1000%, small strain: 1%) was used.
[0088] The experimental results are as follows Figure 2 As shown, the results show that the hydrogel prepared in Example 2 of the present invention has excellent rheological properties and self-healing ability.
[0089] When conductive nanofillers (such as metal nanoparticles, carbon nanotubes, graphene and MXene) are uniformly dispersed in the hydrogel matrix, interconnected electron paths can be formed, thereby enhancing the overall conductivity of the hydrogel. The resistivity of the hydrogels prepared in Example 1, Examples 4-5 and Comparative Example 1 was measured using a four-probe method.
[0090] The experimental results are as follows Figure 3As shown in the figure, the results show that compared with Comparative Example 1, the conductivity of the TAlg / PEDOT@PMOF hydrogel prepared in the embodiment of the present invention is similar to that of the healthy myocardium (~10 -4 S cm -1 ), this hydrogel can couple with myocardial electrophysiology, improve cardiac function, and avoid inducing arrhythmia. The conductivity of the hydrogel prepared in Example 5 of the present invention is 7.78±0.06×10 -4 S cm -1 .
[0091] 3. Nanofiller morphology and catalytic activity detection The nanofiller PEDOT@PMOF prepared in Example 1 was characterized by microscopic morphology, and the elemental composition and distribution of PEDOT@PMOF were analyzed by high-angle annular dark field HAADF mode of STEM.
[0092] The results are as follows Figure 4 As shown, the uniform distribution of elements such as Mn and S in the nanofiller PEDOT@PMOF structure can be clearly observed, proving the existence of the Mn element in the MOF structure and the successful polymerization of PEDOT in the MOF pores and surface.
[0093] In vitro, the SOD-like performance of the nanofiller PEDOT@PMOF was tested in the reaction system of xanthine and xanthine oxidase. -1 ) were respectively mixed with xanthine (0.15 mmol / L) and xanthine oxidase (0.02 U mL -1 ) were mixed in a Tris-HCl buffer with a pH value of 7.0. After incubation at room temperature for 5 min, 0.05 mmol / L NBT was added to each mixed solution. The superoxide generated by the reaction reduced the color developer NBT to blue formazan, which has strong absorption at 560 nm of ultraviolet light. Figure 5 As shown in Figure a, as the concentration of PEDOT@PMOF increases, the absorption peak intensity weakens and the content of superoxide anions decreases, indicating that the SOD-like activity is stronger, proving that it has a dose-dependent SOD-like activity. At the same time, the EPR technology was used to investigate the scavenging efficiency of nanofillers on superoxide free radicals. Figure 5As shown in Figure b, DMPO, as a common free radical scavenger, can capture short-lived superoxide radicals in methanol solvent. In the system without the addition of nanofillers, the peak signal of superoxide radicals is strong, showing a typical six-peak structure of four large and two small. After adding three kinds of nanofillers respectively, the peak intensity is significantly reduced, and as the test time increases, the superoxide radical signal gradually weakens. Unstable superoxide anions are converted into hydroxyl radicals after combining with hydrogen ions. In vitro, hydroxyl radicals are generated based on the Fenton reaction system, and then react with salicylic acid to produce a chromogenic group. As shown Figure 5 As shown in Figure a, with the addition of PEDOT@PMOF and the increase in concentration, the maximum absorption wavelength intensity at 510 nm gradually decreases. Figure 5 The EPR results in Figure c show that after 6 minutes of microwave irradiation, four peaks characteristic of hydroxyl radicals were detected, with peak intensities of 1:2:2:1 from left to right. After adding MOF, PMOF and PEDOT@PMOF respectively, the free radical signals weakened successively, and the signal basically disappeared in the spectrum of the PEDOT@PMOF group at the 12th minute. Under pathological conditions, the process of converting oxygen molecules into water molecules in cells is hindered, and superoxide anions combine with hydrogen ions and generate hydrogen peroxide under the catalysis of superoxide dismutase. In vitro, the CAT enzyme-like properties of a series of prepared nanomaterials were detected based on the redox reaction between titanium sulfate and hydrogen peroxide and the optical properties of its product, peroxide-titanium complex. Figure 5 As shown in Figure d, the absorbance value around 405 nm decreases with the increase of PEDOT@PMOF concentration.
[0094] IV. In vivo effectiveness testing of hydrogel To study the effect of injectable hydrogels with redox activity and electroactivity in repairing cardiac damage in vivo, a rat myocardial infarction model was established by permanent ligation of the left anterior descending branch of the heart, and ultrasound examinations were performed on the rats with successfully modeled myocardial infarction on the 7th, 14th and 28th days.
[0095] The models were implanted with the hydrogels prepared in Example 1, Comparative Example 1 and Comparative Example 2, and 30 μL of the hydrogels were injected into the infarct center and infarct edge using a 27G needle.
[0096] M-mode echocardiography results Figure 6 As shown in Figure 2, compared with the control group, the ventricular wall contraction-diastolic movement in the hydrogel group 3 was significantly improved; the Masson staining results on the 28th day were as follows Figure 7 As shown, compared with the control group, the ventricular wall thickness of the heart tissue in the hydrogel group prepared in Example 1 of the present invention was the highest, and the scar area was the smallest, indicating that the hydrogel prepared in Example 1 effectively reduced the scar area at the site of myocardial infarction, proving that its cardiac repair function is good.
[0097] 5. In vivo testing of hydrogels to reduce susceptibility to arrhythmias Arrhythmia inducibility was assessed 4 weeks after hydrogel injection using a standard clinical programmed electrical stimulation (PES) protocol. PES studies were performed using a stand-alone programmable stimulator, and arrhythmia inducibility was quantified as an inducibility quotient based on a recognized scoring system, with the higher the score, the more arrhythmic inducibility.
[0098] The experimental results are as follows Figure 8 As shown, under programmed electrical stimulation, the arrhythmia induction quotient of the rats treated with the hydrogel prepared in Example 1 of the present invention was the lowest, close to that of the sham operation group. The experimental results show that the third group of hydrogels has good electrical coupling properties and can promote electrical conduction between myocardial tissues.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an injectable hydrogel having redox activity and electroactivity, characterized in that: The following steps are involved: (1) Methacrylic anhydride and polysaccharide molecules are reacted in a solvent to prepare a double-bond functional polymer; (2) Dopamine is first prepolymerized in a solvent, and then a metal framework compound is added to carry out a polymerization reaction to obtain a dopamine-modified metal framework compound; (3) reacting the dopamine-modified metal framework compound obtained in step (2), 4-ethylenedioxythiophene and iron salt in a solvent, collecting the precipitate, and preparing a nanofiller; (4) The double-bond functional polymer obtained in step (1), the active polypeptide, the photoinitiator and the nanofiller obtained in step (3) are dispersed together in a solvent to obtain a reaction solution, and then photocured and cross-linked to obtain the product.
2. The method for preparing the injectable hydrogel having redox activity and electroactivity according to claim 1, characterized in that: In the step (1), the polysaccharide molecule is sodium alginate, the solvent is water, the reaction temperature is 0-10°C, and the reaction time is 20-30 h.
3. The method for preparing the injectable hydrogel having redox activity and electroactivity according to claim 1, characterized in that: The metal framework compound in step (2) is prepared by the following steps: (a) reflux methyl p-formylbenzoate and pyrrole in a solvent to obtain a purple solid product; (b) refluxing the purple solid product obtained in step (a) and manganese chloride tetrahydrate in a solvent, then adding water and stirring after the solution is cooled to room temperature, and collecting the precipitate; (c) first dissolving the precipitate obtained in step (b) in an organic solvent, then mixing with a KOH aqueous solution and refluxing, then removing the organic solvent by rotary evaporation, adding water for redissolution, and finally adding an acidic solution to precipitate and collect a solid to obtain a purple powder product; (d) zirconium oxychloride octahydrate, benzoic acid and the purple powder product obtained in step (c) are mixed in a solvent for reaction, and the precipitate is collected to obtain the product.
4. The method for preparing the injectable hydrogel having redox activity and electroactivity according to claim 3, characterized in that: In step (a), the solvent is propionic acid and the reflux time is 10-15 h; In step (b), the solvent is N,N-dimethylformamide, the reflux time is 4-8 h, and the stirring time is 30-90 min; In step (c), the organic solvent is a mixed solvent consisting of tetrahydrofuran and methanol, and the mixing and reflux time is 10-15 hours; The temperature of the mixed reaction in step (d) is 80-100° C. and the time is 4-6 h.
5. The method for preparing the injectable hydrogel having redox activity and electroactivity according to claim 1, characterized in that: In the step (2), the solvent is a Tris-HCl solution, the prepolymerization time is 20-40 min, and the polymerization reaction time is 10-15 h.
6. The method for preparing the injectable hydrogel having redox activity and electroactivity according to claim 1, characterized in that: In step (3), the solvent is ethanol, the iron salt is ferric chloride hexahydrate, and the reaction conditions are stirring in an ice bath for 20-30 hours.
7. The method for preparing the injectable hydrogel having redox activity and electroactivity according to claim 1, characterized in that: The amino acid sequence of the active polypeptide in step (4) is shown in SEQ ID NO.
1.
8. The method for preparing the injectable hydrogel having redox activity and electroactivity according to claim 1, characterized in that: In step (4), the solvent is water; The concentration of the double bond functional polymer in the reaction solution is 1 w / v %-5 w / v %; The concentration of the photoinitiator is 0.1 w / v %-0.5 w / v %; The mass ratio of active polypeptide to double-bond functional polymer is 0.1:1-1:1; The concentration of nanofillers was 10-80 μg / mL; The conditions for photocuring crosslinking are: irradiation with 350-450 nm ultraviolet light for 30-60 s.
9. An injectable hydrogel having redox activity and electroactivity, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.
10. Use of the injectable hydrogel having redox activity and electroactivity according to claim 9 in the preparation of a medicament for treating heart failure.
Citation Information
Patent Citations
Preparation method and application of conductive hydrogel capable of slowly releasing drugs and factors
CN109265709A
Polypeptide, and production method and application thereof
CN109593126A
Composition containing recombinant III-type humanized collagen as well as preparation method and application of composition
CN113713086A
Injectable hydrogel with anti-inflammatory and repair-promoting functions, preparation method of injectable hydrogel and application of injectable hydrogel in heart repair
CN114585396A
Transcatheter injectable conductive hydrogel for heart failure treatment and preparation method thereof
CN114870038A
Cited By
Type I collagen composition for tissue repair and preparation method thereof
CN121714765A
Type I collagen composition for tissue repair and its preparation method
CN121714765B
Preparation method of high-modulus polycaprolactone polyethylene glycol copolymer hydrogel
CN121779742A
An induced melting entanglement electroactive hydrogel with myocardial repair performance, a preparation method and application thereof
CN122682096B